SSR marker based differentiation of zygotic and nucellar seedlings in mango (Mangifera indica) - KUMAR, KAMLESH; SRIVASTAV, MANISH; SINGH, SANJAY KUMAR; SINGH, ANKIT (The Indian Journal of Agricultural Sciences, 2020)
Non-availability of standard clonal rootstocks in mango (Mangifera indica L.) is considered as an important hurdle, which has significant impact on orchard productivity. To obtain grafted mango plants, it is important to use polyembryonic rootstocks since they produce a zygotic and several nucellar plantlets from their seed, which are trueto- the type and also uniform. It is therefore imperative to device some reliable approach to ascertain the nucellar origin of seedlings to be used as rootstocks and thus culling out the variable zygotic seedlings in a polyembryonic genotypes for their use as uniform clonal rootstock. Differentiation of zygotic and nucellar seedlings using SSR markers in mango rootstock genotypes was undertaken during 2012-2015. Of the 42 SSRs used, 9 primer pairs (LMMA1, LMMA2, LMMA8, LMMA15, ESTD1, ESTD2, ESTD6, ESTD9 and ESTD10) were found to be informative, while 33 primer pairs were monomorphic. These nine primer pairs were used for differentiating zygotic and nucellar seedlings. In Olour rootstock, LMMA1, LMMA2, LMMA8, ESTD6 and ESTD10 primer pairs were informative and ascertained the zygotic and nucellar origin of seedlings. In Kurukkan rootstock, ESTD1, ESTD2, ESTD6 and ESTD9 primer pairs differentiated zygotic from nucellar seedlings. In 13-1 rootstock, LMMA8, LMMA15 and ESTD9 discriminated nucellars from zygotic seedlings. It is concluded that SSR markers were useful in differentiating the zygotic and nucellar seedlings in polyembryonic mango rootstocks and can be used in combinations to ascertain the origin of seedlings in polyembryonic mango rootstocks.